Techniques of TV interviewing - Minehan, Mike.; First Light Video Publishing (Los Angeles, CA : First Light Video Pub., 2005)
Looks at important aspects of interviewing by examining interviews done on Australian Current Affairs TV programs in 1975.
Written and produced by Mike Minehan.
Keywords: Interviewing on television; Talk shows; Television broadcasting of news